Reflexivity and an Arts-based Inquiry during Covid-19 times - Kuhnke, Janet Lynne (European Journal for Qualitative Research in Psychotherapy, 2021)
This paper examines the role of reflexivity and arts-based activities as a medium for reflexivity, during Covid-19 times. Using an autobiographical performative inquiry research methodology, the role of reflexive practice and art-based activities are explored as part of managing during times of crisis. The author considers Covid-19 as a ‘stop’; a stop is a moment in time when attention is called forward from life events. Stops are moments that interrupt one’s life, and that evoke new questioning of what could be and to consider new possibilities. To understand this process the life of Emily Carr, a Canadian artist, is reflected upon to explore the emotions surrounding critical life events as related to ones’ well-being. Finally, the role of pushing back in challenging times is travelled; and finally, death is explored as part of life.